Sustainable Work: Seven case studies on social-ecological implications in Europe - Ernest Aigner; Lucia Baratech Sanchez; Desiree Alicia Bernhardt; Benjamin Curnow; Christian Hödl; Heidi Leonhardt; Anran Luo (WWWforEurope, 2016)
In a highly globalised world where all production and consumption activities are internationally intertwined and the environmental consequences of those actions are hard to identify, rethinking the role of work in our societies according to sustainability principles is a complex but highly necessary task. Salaried work has become one of the crucial indicators to analyse any country in the world. By looking at the proportion of the population that is employed, the working conditions they have, and how productive they are when performing their tasks, it is possible to produce an image of a country's society to assist in the understanding of the levels of well-being of its citizens. Work and labour markets not only largely structure the way the economy and society function, they also heavily influence an individual's life satisfaction and happiness; virtually the entire life of a person is designed around their work. Given the relevance work has at all levels, diving into the concept of sustainable work is a crucial project due to the urgency of environmental matters. The biggest role humanity faces is how to transform our societies so that they are sustainable from a social, ecological and economic perspective. For the sustainable society vision, work would need to be drastically altered in order to adapt it to the multi-dimensional sustainability requirements. This research aims to contribute to this enterprise by identifying the conditions that define the sustainability of work and then present an overview of seven European countries from this perspective. The present document introduces our conceptualisation of work and explains its main components. These are designed around the idea of the sustainable society and are composed of individuals' needs, equity and planetary boundaries. The final section concludes and introduces the different country-case studies.
Keywords: 330; Arbeitsplatzteilung; Nachhaltige Entwicklung; EU-Staaten